2021
DOI: 10.3390/cancers13215406
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor-4 Antagonist Enhances the Repair of Ultraviolet Radiation-Induced DNA Damage and Augments Anti-Tumor Immune Responses in Mice

Abstract: Ultraviolet (UV) irradiation of the skin is related to the development of skin cancer. UVB also causes DNA damage in the form of cyclobutane pyrimidine dimers (CPDs), which can result in stable mutations. Toll-like receptor 4 (TLR4), a component of innate immunity, plays a key role in cancer. Previous studies from our laboratory have observed that TLR4 deficiency resulted in the repair of UVB-induced DNA damage, inhibition of UVB-induced immune suppression, and carcinogenesis. In this study, we determined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Malignant transformation of melanocytes is a very complex, multi-step process that involves several genes orchestrating cell proliferation, differentiation, apoptosis and antitumor immune responses [1,2]. The accumulation of genetic changes, including UV-driven mutation burdens, makes melanoma a highly immunogenic tumor, suitable for immunotherapy [17][18][19]. However, due to insufficient immune activation, patients show variable response rates to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malignant transformation of melanocytes is a very complex, multi-step process that involves several genes orchestrating cell proliferation, differentiation, apoptosis and antitumor immune responses [1,2]. The accumulation of genetic changes, including UV-driven mutation burdens, makes melanoma a highly immunogenic tumor, suitable for immunotherapy [17][18][19]. However, due to insufficient immune activation, patients show variable response rates to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Also, deubiquitinating enzyme tripartite motif-containing protein 44 (TRIMM44) promotes melanoma progression via TLR4 stabilization, which subsequently activates the phosphoinositide 3-kinase-AKT-mammalian target of rapamycin signaling pathway [27]. Finally, treatment with TLR4 antagonist TAK-242 amplifies antitumor immune responses in UV-induced skin cancer in mice [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAK-242 ( 2 , resatorvid, CLI-095), a selective TLR4 signaling inhibitor (Figure ), covalently binds to Cys747 on the intracellular domain of TLR4 via Michael reaction, disrupting the interaction between TLR4 and cohesion molecules and inhibiting NO, TNF-α, and IL-6 production, with IC 50 values of 1.8, 1.9, and 1.3 nM, respectively. , TAK-242 ( 2 ) blocks UV-induced NF-κB and MAP kinase/AP-1 activity and the expression of cytokines IL-6, IL-8, and IL-10 in cultured keratinocytes and the skin of topically treated mice, showing potential for prevention of nonmelanoma skin cancer (NMSC). , Subsequent studies demonstrated that treatment with 2 increased the level of expression of xeroderma pigmentosum group A (XPA) mRNA, resulting in the repair of UVB-induced cyclobutane pyrimidine dimers (CPDs) in the skin of SKH-1 mice. Treatment with 2 inhibited the expression of pro-inflammatory cytokines IL-1β, IL-6, and TNF-α and enhanced the antitumor immune response in mice …”
Section: Therapeutic Modulators Of Tlrsmentioning
confidence: 99%
“…Using iQ TM SYBR Green Master Mix (Bio-Rad, Hercules, CA, USA), cDNA was amplified by a real-time PCR with a Bio-Rad MyiQ thermocycler and SYBR Green detection system (Bio-Rad, Hercules, CA, USA). The standard PCR conditions were 95 • C for 10 min and then 40 cycles at 95 • C for 30 s, 60 • C for 30 s, and 72 • C for 30 s. The expression of XPA, IFNα, IFNβ, IRF1, IRF4, IRF7 gene (Table 1) was normalized to the expression level of the GAPDH mRNA in each sample (23,40,(44)(45)(46)(47)(48)(49)(50). For mRNA analysis, the calculations for determining the relative level of gene expression were made using the cycle threshold (C t ) method.…”
Section: Rna Extraction and Quantitative Real-time Pcr (Qpcr)mentioning
confidence: 99%